Uncertainty avoidance: public sector clients and procurement selection - Love, Peter; Davis, Peter; Edwards, D.; Baccarini, David (Emerald Group Publishing Ltd, 2008)
Purpose – Choosing the appropriate procurement system for construction projects is a complex and challenging task for clients particularly when professional advice has not been sought. To assist with the decision‐making process, a range of procurement selection tools and techniques have been developed by both academic and industry bodies. Public sector clients in Western Australia (WA) remain uncertain about the pairing of procurement method to bespoke construction project and how this decision will ultimately impact upon project success. This paper seeks to examine “how and why” a public sector agency selected particular procurement methods. Design/methodology/approach – An analysis of two focus group workshops (with 18 senior project and policy managers involved with procurement selection) is reported upon. Findings – The traditional lump sum (TLS) method is still the preferred procurement path even though alternative forms such as design and construct, public‐private‐partnerships could optimize the project outcome. Paradoxically, workshop participants agreed that alternative procurement forms should be considered, but an embedded culture of uncertainty avoidance invariably meant that TLS methods were selected. Senior managers felt that only a limited number of contractors have the resources and experience to deliver projects using the non‐traditional methods considered. Practical implications – The research identifies a need to develop a framework that public sector clients can use to select an appropriate procurement method. Learning from previous experiences with regard to procurement selection will further provide public sector clients with knowledge about how to best deliver their projects. Originality/value – The paper adds insight as to how public sector agencies select particular procurement methods.